2018
DOI: 10.1093/jac/dky064
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Oxadiazole antimicrobials act synergistically with daptomycin and display rapid kill kinetics against MDR Enterococcus faecium

Abstract: The 1,2,4-oxadiazoles are active against MDR and daptomycin-non-susceptible E. faecium and hold great promise as future therapeutics for treating infections caused by these difficult-to-treat isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our previous findings demonstrated that compound 1 also displayed potent activity against a range of clinically relevant E. faecium strains, including both VREfm and daptomycin-resistant strains. 31 Compound 1 was not toxic against the human cell line HepG2 at the E. faecium MIC 90 (2 μg/mL); however, reduced viability was observed at higher concentrations. This was deemed to represent a potentially narrow therapeutic window, but analogues of compound 1 have been reported by Spink et al in 2015 with activity against S. aureus and reduced toxicity against HepG2 cells.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Our previous findings demonstrated that compound 1 also displayed potent activity against a range of clinically relevant E. faecium strains, including both VREfm and daptomycin-resistant strains. 31 Compound 1 was not toxic against the human cell line HepG2 at the E. faecium MIC 90 (2 μg/mL); however, reduced viability was observed at higher concentrations. This was deemed to represent a potentially narrow therapeutic window, but analogues of compound 1 have been reported by Spink et al in 2015 with activity against S. aureus and reduced toxicity against HepG2 cells.…”
Section: Resultsmentioning
confidence: 89%
“…1 has previously been shown to possess membrane-lytic activity, with concentrations in excess of 64 μg/mL leading to haemolysis in human erythrocytes. 31 To determine whether 15e displayed a similar membrane-lytic activity as 1 , the compound was tested against human erythrocytes as before ( Figure 4 c). Limited haemolysis was observed following incubation of human erythrocytes with 4 μg/mL 15e (approximate MIC of C. difficile and E. faecium ), with only 2.5% (range: 0–7%) of erythrocytes undergoing lysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we came up with an idea to examine 1,2,4-oxadiazole ring as an alternative core for the promising 2-imidazoline-containing periphery, as it could provide novel two-heterocycles-hybrid based series of compounds for further diverse biological evaluation. These expectations were supported by several successful series of variously biologically active oxadiazoles synthesized and evaluated in our group [7,8,9,10], as well as by recent example of anti-MRSA (Methicillin-Resistant Staphylococcus aureus ) and anti-VRE (Vancomycin-Resistant Enterococcus ) active antibiotics incorporating 3-phenoxyphenyl-substituted 1,2,4-oxadiazoles, that have been recently reported [11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 84%
“…Animal experimentation was carried out with approval from the University of Melbourne, Department of Biochemistry and Molecular Biology, Dental Science, Medicine, Microbiology & Immunology, and Surgery Animal Ethics Committee. A total of 6–8 weeks old female C57BL/6 mice were infected with either the daptomycin-susceptible strain DMG1800332, or daptomycin-resistant clinical isolates DMG1901766, DMG1700661 ( Carter et al, 2018 ), or DMG1700787. Mice were infected via intraperitoneal injection with 10 9 CFU resuspended in sterile rat faecal extract (SRFE) ( Singh et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%